Expression of CD117, DOG-1, and IGF-1R in gastrointestinal stromal tumours – an analysis of 70 cases from 2004 to 2010 - Kiśluk, Joanna; Zińczuk, Justyna; Kemona, Andrzej; Guzińska-Ustymowicz, Katarzyna; Żurawska, Joanna; Kędra, Bogusław (Gastroenterology Review/Przegląd Gastroenterologiczny, 2016)
Introduction : Determination of the type of mutations in gastrointestinal stromal tumours (GIST) plays a major role in assessing the risk of progression of the disease, and also allows determination of the clinical management and treatment. More accurate GIST diagnosis is possible by using simultaneously various types of antibodies to immunohistochemistry methods in routine procedures. Aim : To evaluate the expression of CD117, DOG-1, and IGF-1R in patients with gastrointestinal stromal tumours, and analysis of the impact of the examined protein expression on patient survival with emphasis on specific recognition and prognostication of these tumours. Material and methods : The protein expression was analyzed in 70 patients who had undergone surgical treatment for mesenchymal tumours of the gastrointestinal tract, using the immunohistochemical method. Results : Positive expression of CD117, DOG-1, and IGF1R included 95.71%, 88.57% and 11.43% of study GISTs, respectively. Statistical analysis showed positive significant correlation between DOG-1 expression and histological type of tumour (p = 0.024). Analysis of overall survival curves of 70 GIST patients according to expression of CD117, DOG-1, and IGF1R did not show a tendency towards longer survival of patients with positive expression (p > 0.05). Conclusions : Predictive factors determining the survival time of patients are strongly associated with morphological features of tumours. A thorough analysis of each case plays a key role in predicting survival time of patients and may be a clue in targeting the therapeutic procedure.